1957
DOI: 10.1038/bjc.1957.6
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Cell Type in Relation to the Aetiology of Lung Cancer

Abstract: KREYBERG (1952KREYBERG ( , 1954aKREYBERG ( , b, c, d, and 1955 has concluded that the histological types of lung cancer to be seen in Norway can be divided into two aetiologically distinct groups. The squamous cell, large cell and small cell carcinomas (including oat-cell carcinomas) form the first group. These types he thought might be histological variants of a single oncological entity and be produced largely by exposure to an external factor (or factors) which have recently increased in prevalence and to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
1
2

Year Published

1959
1959
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 2 publications
0
24
1
2
Order By: Relevance
“…Originally, adenocarcinoma was considered to occur primarily among non-smokers (Doll et al, 1957;Kreyberg, 1961), but later studies demonstrated that it is also strongly associated with smoking (Thun et al, 1997;Simonato et al, 2001;Yang et al, 2002). The increased incidence of adenocarcinoma among smokers may be explained by the widespread introduction of filter and lower-tar and nicotine cigarettes (Wynder and Muscat, 1995;Stellman et al, 1997;Thun et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, adenocarcinoma was considered to occur primarily among non-smokers (Doll et al, 1957;Kreyberg, 1961), but later studies demonstrated that it is also strongly associated with smoking (Thun et al, 1997;Simonato et al, 2001;Yang et al, 2002). The increased incidence of adenocarcinoma among smokers may be explained by the widespread introduction of filter and lower-tar and nicotine cigarettes (Wynder and Muscat, 1995;Stellman et al, 1997;Thun et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Usually the character of the pathological material has been known to the pathologist. When observer bias is nevertheless assumed to be negligible as a cause of variation it is mainly for the following reasons: Firstly, Kreyberg, who has undertaken by far the greater part of the typing, has repeatedly demonstrated that his classification, under varying conditions, including blind trials, is highly consistent (Doll, Hill and Kreyberg, 1957;Kreyberg and Saxen, 1961 Table II shows that their age pattern a steady increase with age differs markedly from that of all histologically confirmed cases. It is indeed possible that this undetermined group or that part of it which really is primary lung cancer contains the varying histological types in proportions different from those observed in the histologically examined group.…”
Section: Discussionmentioning
confidence: 99%
“…In the mid-20 th century, small cell and squamous cell carcinoma were the most common types of lung cancer diagnosed in many parts of the world (9). At that time, many researchers and clinicians even doubted whether adenocarcinoma was associated with cigarette smoking (10). Over time, the prevalence of adenocarcinoma has increased markedly to the point where it is now the most common major lung cancer cell type throughout much of the world (11), regularly diagnosed in both smokers and never-smokers.…”
mentioning
confidence: 99%